Technological change and workers' movements / edited by Melvyn Dubofsky (London, 1985)
An unusual opportunity to compare the social science perspectives that prevail in the United States and the Soviet Union was provided at the third U.S.-U.S.S.R. Colloquium on World Labor and Social Change. The articles in this collection derive from that colloquium, co sponsored by the American Council of Learned Societies and the U.S.S.R. Academy of Science's Commission on Humanities and Sciences. The Soviet and American contributors to this volume range widely in the focus of their scholarship-some analyses are historical, others have a more contemporary focus. Both developed and developing capitalist and socialist states are examined. Taken together, these analyses illustrate the different ways scholars in the respective countries approach common issues: technological change, economic and social structure, and working class behavior. The collection will serve as an important reference volume for researchers in sociology, world-systems, history, and other fields concerned with technology and labor.
Keywords: Technological innovations - History